Assessment of strategies to increase chondrocyte viability in cryopreserved human osteochondral allografts: evaluation of the glycosylated hydroquinone, arbutin - Rosa, Susana Carvalho (2009)
Objective: Allogeneic cartilage is used to repair damaged areas of articular cartilage, requiring the presence of living chondrocytes. So far, no preservation method can effectively meet that purpose. Identification of more effective cryoprotective agents (CPAs) can contribute to this goal. The aim of this study was to determine whether the glycosylated hydroquinone, arbutin, alone or in combination with low concentrations of other CPAs, has cryoprotective properties towards human articular cartilage. Material and methods: Human tibial plateaus were procured from multi-organ donors, with the approval of the Ethics Committee of the University Hospital of Coimbra. The tibial plateaus were treated with or without arbutin (50 or 100 mM), alone or in combination with various concentrations of dimethyl sulfoxide (DMSO) and glycerol, for 0.5e1.5 h/37 C, then frozen at 20 C and 24 h later transferred to a biofreezer at 80 C. Two to 3 months later, thawing was achieved by immersion in cell culture medium at 37 C/1 h. Chondrocyte viability was assessed before and after freezeethawing using a colorimetric assay based on the cell’s metabolic activity and fluorescent dyes to evaluate cell membrane integrity. Results: Before freezing, chondrocyte metabolic activity was identical in all the conditions tested. After freezeethawing, the highest activity, corresponding to 34.2 2.1% of that in the Fresh Control, was achieved in tibial plateaus incubated in 50 mM arbutin for 1 h whereas in those left untreated it was 11.1 4.7. Addition of DMSO and glycerol to arbutin did not increase chondrocyte viability any further. Fluorescence microscopy confirmed these results and showed that living chondrocytes were mainly restricted to the superficial cartilage layers. Conclusion: Arbutin seems to be an effective cryoprotective agent for osteochondral allografts with potential benefits over DMSO and glycerol.